The effect of antecedent variables to improve performance while working from home: Study of teachers at private school in Greater Jakarta - Sylvia Diana Purba; Herry Pramono; Diona Christy; Yusman Yacob; Efendi Efendi (Jurnal Manajemen dan Pemasaran Jasa, 2024)
During the pandemic, many work activities were carried out online, which was called Work from Home (WFH). Likewise, teaching and learning activities in schools are also affected by the online system in the distance teaching and learning process. This research was conducted during the pandemic to determine job satisfaction and performance of teachers with the job characteristic model, subjective well-being, and work climate as variable antecedents during WFH work where job satisfaction is a mediating variable in improving performance. The research was carried out at a private school foundation in the surrounding area of ​​Jakarta. The research respondents were 118 teachers using a convenience data sampling technique using a questionnaire with a Likert scale. The research model uses SEM and data is processed with PLS version 3.0 software. Job Characteristics significantly increase job satisfaction and job performance. Subjective Well-Being can increase Job satisfaction but cannot increase Job Performance, whereas Job satisfaction can fully mediate Subjective Well-Being in increasing Job Performance. On the other hand, job satisfaction can mediate job characteristics on job performance, but not as strongly because the direct influence is stronger. Likewise, at the marginal level, work climate can increase job satisfaction but cannot increase job performance and job satisfaction cannot mediate the influence of work climate on job performance.